Urban Malaysian Adolescents' Online Activities. - Tan, Kok Eng; Ng, Melissa, Lee Yen Abdullah; Saw, Kim Guan (2009)
Many Malaysian adolescents are immersed in the global contemporary,technological and digital culture. Their everyday literacy practices involve participation in a range of activities on the Internet.